Mechanism and Physiologic Significance of the Suppression of Cholesterol Esterification in Human Interstitial Fluid - Miller, Norman E.; Olszewski, Waldemar L.; Miller, Irina P.; Nanjee, Mahmud N. (Frontiers in Pharmacology, 2016)
Cholesterol esterification in high density lipoproteins (HDLs) by lecithin:cholesterol acyltransferase (LCAT) promotes unesterified cholesterol (UC) transfer from red cell membranes to plasma in vitro. However, it does not explain the transfer of UC from most peripheral cells to interstitial fluid in vivo, as HDLs in afferent peripheral lymph are enriched in UC. Having already reported that the endogenous cholesterol esterification rate (ECER) in lymph is only five per cent of that in plasma, we have now explored the underlying mechanism. In peripheral lymph from 20 healthy men, LCAT concentration, LCAT activity (assayed using an optimized substrate), and LCAT specific activity averaged respectively 11.8, 10.3, and 84.9 per cent of plasma values. When recombinant human LCAT was added to lymph, the increments in enzyme activity were similar to those when LCAT was added to plasma. Addition of apolipoprotein AI (apo AI), fatty acid-free albumin, Intralipid, or the d<1.006 g/ml plasma fraction had no effect on ECER. During incubation of lymph plus plasma, the ECER was similar to that observed with buffer plus plasma. When lymph was added to heat-inactivated plasma, the ECER was 11-fold greater than with lymph plus buffer. Addition of discoidal proteoliposomes of apo AI and phosphatidycholine (PC) to lymph increased ECER ten-fold, while addition of apo AI/PC/UC discs did so by only six-fold. We conclude that the low ECER in lymph is due to a property of the HDLs, seemingly substrate inhibition of LCAT by excess cell-derived UC. This is reversed when lymph enters plasma, consequent upon redistribution of UC from lymph HDLs to plasma lipoproteins.